ANALISIS PERSEPSI KEPUASAN DALAM MENINGKATKAN LOYALITAS MAHASISWA DENGAN MENGGUNAKAN RELATIONSHIP MARKETING DAN SERVQUAL - Aswin - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2014)
The research is done in Informatics & Business Institute Darmajaya, the reason why ischosen IBI Darmajaya as research object because in 2010 it was chosen in 56 the best universityquality guaranty version dikti and in 2008 got ISO 9001 certificate. However, the condition has notgot the students yet, it is shown by lees of the number of students at learning finishing process andaverage score of service given by students was in still low score. The purpose of this research is toanalyze relationship marketing effects, service quality toward satisfactory in increasing students’loyalty.The result of this research shows that Relationship Marketing influences significantly andpositively toward students’ satisfactory. Service quality influences significantly and positively towardstudents’ satisfactory. Relationship marketing influences significantly and positively toward students’loyalty. Service quality influences significantly and positively toward students’ loyalty. Students’satisfactory influences significantly and positively toward students’ loyalty. Relationship marketinginfluences significantly and positively toward service quality. The result of this research indicates thatto increase IBI Darmajaya students’ loyalty must pay attention some factors such as relationshipmarketing, service quality and students’ satisfactory because those factors are proven influencingthe high low of students’ loyalty.